Factors Associated with Occurence of Postoperative Surgical-Site Infection and Length of Hospitalization in Children with Intussusception - Leecarlo M. Lumbangaol (Fakultas Kedokteran Universitas Kristen Indonesia, 2016)
Abstract Surgical-site infection (SSI) is one of the most common surgical post-laparotomy complications, either manual reduction or resection anastomotic, such as intussusception case. This retrospective cohort study aimed to identify factors associated with occurrence of postoperative surgical-site infection and length of hospitalization using medical records in Tarakan District Hospital from January 2014 to December 2015. Odds ratios and 95% confidence intervals were calculated to evaluate the association between potential clinical factors and the occurrence of surgical-site infection as well as length of hospitalization. Sepsis, perioperative level of hemoglobin, and the type of postoperative ward were found potentially increase the risk of the occurrence of surgical-site infection. Low preoperative level of albumin and Hemoglobin, prolonged surgery, postoperative sepsis, hospitalized in the pediatric intensive care unit (PICU) ward and resection were also increased the risk of longer hospitalization in patients with intussusceptions. It is hoped that interventions to prevent the occurrence of SSI and to shorten the length of hospitalization among children with intussusceptions in Tarakan District Hospital can take place in the future. Key Words: risk factors, intussusception, surgical-site infection, length of hospitalization Abstrak Infeksi pada luka operasi (surgical-site infection, SSI) adalah salah satu komplikasi bedah yang paling umum pasca laparotomi, termasuk kasus intususepsi. Studi kohort retrospektif ini bertujuan untuk mengidentifikasi faktor yang berhubungan dengan terjadinya infeksi luka pasca operasi dan lama rawat inap dengan menggunakan catatan medis di RSUD Tarakan dari Januari 2014 sampai Desember 2015. Odds ratio dan interval kepercayaan 95% dihitung untuk mengevaluasi hubungan antara faktor klinis dan terjadinya infeksi luka operasi serta lama rawat inap. Sepsis, kadar hemoglobin perioperatif, dan lokasi rawat PICU ditemukan berpotensi meningkatkan risiko terjadinya SSI. Rendahnya kadar albumin dan Hb praoperasi, durasi operasi yang lama, sepsis pasca operasi, dirawat di pediatric intensive care unit (PICU) dan reseksi juga meningkatkan risiko rawat inap yang lebih lama pada pasien dengan intususepsi di RSUD Tarakan. Dengan pengetahuan ini, diharapkan bahwa intervensi untuk mencegah terjadinya SSI dan untuk memperpendek lama rawat inap pada anak-anak dengan intususepsi di RSUD Tarakan dapat dilakukan di masa depan. Kata kunci: faktor risiko, intususepsi, infeksi luka operasi, lama rawat